2021
DOI: 10.1186/s41687-021-00379-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the content validity of patient-reported outcome (PRO) instruments developed for use with individuals with phakic presbyopia, including the Near Activity Visual Questionnaire-presbyopia (NAVQ-P) and the near vision correction independence (NVCI) instrument

Abstract: Background Presbyopia is the age-related deterioration in the ability to focus on close objects. In order to develop a patient-reported outcome (PRO) instrument to assess near vision functioning, the Near Activity Visual Questionnaire (NAVQ) was adapted to incorporate modern technology (e.g. smartphones) and to be appropriate for use in phakic presbyopia, leading to the development of the NAVQ-Presbyopia (NAVQ-P). Additional single-item instruments of near vision correction independence (NVCI),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…32 The Near Activity Visual Questionnaire and Near Activity Visual Questionnaire-Presbyopia might be more sensitive to detect differences between IOLs, but they lack clinically relevant information about dysphotopsia and spectacle independence at several distances provided by questionnaires measuring other domains, such as the Quality of Vision or the Patient-Reported Spectacle Independence Questionnaire. [35][36][37] This fact explains why researchers usually use their own nonvalidated questionnaires, or they extract single questions from validated questionnaires to collect data of clinical relevance in this population. 38 The researcher should decide the validated questionnaire that better fits the domain that is intended to measure, but from a clinically relevant perspective and for enabling the between-study comparison, there are single questions for which reporting the proportion of subjects achieving a particular level in a 5-point Likert scale could be of great relevance for studies with short-term follow-ups (<6 months).…”
Section: Defocus Curvesmentioning
confidence: 99%
See 1 more Smart Citation
“…32 The Near Activity Visual Questionnaire and Near Activity Visual Questionnaire-Presbyopia might be more sensitive to detect differences between IOLs, but they lack clinically relevant information about dysphotopsia and spectacle independence at several distances provided by questionnaires measuring other domains, such as the Quality of Vision or the Patient-Reported Spectacle Independence Questionnaire. [35][36][37] This fact explains why researchers usually use their own nonvalidated questionnaires, or they extract single questions from validated questionnaires to collect data of clinical relevance in this population. 38 The researcher should decide the validated questionnaire that better fits the domain that is intended to measure, but from a clinically relevant perspective and for enabling the between-study comparison, there are single questions for which reporting the proportion of subjects achieving a particular level in a 5-point Likert scale could be of great relevance for studies with short-term follow-ups (<6 months).…”
Section: Defocus Curvesmentioning
confidence: 99%
“…32 The Near Activity Visual Questionnaire and Near Activity Visual Questionnaire–Presbyopia might be more sensitive to detect differences between IOLs, but they lack clinically relevant information about dysphotopsia and spectacle independence at several distances provided by questionnaires measuring other domains, such as the Quality of Vision or the Patient-Reported Spectacle Independence Questionnaire. 35–37…”
Section: Patient-reported Outcomesmentioning
confidence: 99%
“…Both individuals with phakic presbyopia and HCPs who were experienced in treating presbyopia were interviewed between February 2018 and July 2019. The interviews also included cognitive debriefing of the Near Activity Vision Questionnaire Presbyopia (NAVQ-P), but those methods and findings are not the focus of the present article [ 30 ]. Ethical approval and oversight was provided by Copernicus Group Independent Review Board (CGIRB; IRB ref: ADE1-18-049), an Independent Review Board (IRB) in the US for the US interviews, prior to any study related activities in the US.…”
Section: Methodsmentioning
confidence: 99%
“…[91][92][93] With time, we have had to develop some further to remain relevant to changing lifestyles and impact of social media, 94,95 especially the ubiquitous digital environment. 96,97 We have demonstrated that they are influenced by whether they are self-completed or the questions are posed to patients, so this needs to remain the same if scores are to be compared over time or across patients/treatments. 98 Traditional patient-reported outcome measures assess only one trait, by design, and so do not account for the patient experience of the management of their condition.…”
Section: Assessment Of Functional Vision Eye Focus/ Accommodationmentioning
confidence: 99%
“…We have been involved in developing quality-of-life questionnaires for macular degeneration, 83,84 visual impairment, 85–90 and presbyopia 91–93 . With time, we have had to develop some further to remain relevant to changing lifestyles and impact of social media, 94,95 especially the ubiquitous digital environment 96,97 . We have demonstrated that they are influenced by whether they are self-completed or the questions are posed to patients, so this needs to remain the same if scores are to be compared over time or across patients/treatments 98 .…”
Section: Instrumentationmentioning
confidence: 99%